Perintah Mengajar dalam Perspektif Tafsir Tarbawi: Telaah Nilai Pendidikan Islam dari Al-Qur'an - Rahmawati, Lady Eka; Putra, Sudarmadi (Nusantara: Jurnal Pendidikan Indonesia, 2023)
This article aims to examine the interpretation of Qur'anic verses related to the basis of the teaching command for all mankind. Teaching obligations are included in the realm of educational studies. The interpretation of verses of the Qur'an related to the field of education is called the term tafsir tarbawi. Formulate the problems including a) what are the teaching vocabulary in the Qur'an, b) how the ulama interpret the verses about teaching, c) the implementation of the educational value of the verses. This research uses a qualitative method and is described in a descriptive manner (content analysis) in the form of library research. The results of the study concluded that the terms teaching in the Qur'an include 'allama (???????), rabbani (??????) and balligh (????). The verses of the obligation to teach are listed in Surah al-Baqarah verse 33 and Surah al-Maidah verse 67. The value of the implementation of education from these two verses makes people realize that teaching is not solely a professional realm but is actually a divine command, as Allah SWT., commanded the Prophet Adam (as), and the Prophet Muhammad (PBUH) to teach.